THE EFFECT OF BUDGETARY GOAL CHARACTERISTICS, FINANCIAL ATTITUDE, PERSONALITY AND INCOME ON FINANCIAL PERFORMANCE OF BATIK BUSINESS ACTORS IN SIDOARJO DISTRICT - Mustofah , Muhammad; Sriyono, Sriyono (PT. Antis International Publisher, 2025)
Objective: The purpose of this study is to determine which one is the most dominant in influencing financial performance. Method: With a population of 932 craftsmen and 100 craftsmen who have worked for more than 1 year as samples. This research method uses quantitative. Data collection techniques using a Likert scale questionnaire. The sampling technique uses the Total Sampling Technique. Data analysis uses SEM PLS. Data processing techniques use Smart PLS 4.0. Hypothesis testing uses the path direct effect test. Results: Budgetary goal characteristics partially have a positive and significant effect on financial performance. Financial attitude variables partially have a positive and significant effect on financial performance. Personality variables partially have a positive and significant effect on financial performance. And income variables also partially have a positive and significant effect on financial performance. Novelty: Micro, Small and Medium Enterprises (MSMEs) in Indonesia are one of the mainstays of the Indonesian economy besides cooperatives.